Effect of Instilling 1 Liter Normal Saline into The Peritoneal Cavity after Laparoscopic Cholecystectomy on Post-Op Pain Relief: A Comparative Analysis - Aisha, Kaneez; Kausar, Muhammad Talha; Shafaq; Saeed, Kanwal; Amin, Hajra; Mansoor, Muhammad Hadi (Indus Journal of Bioscience Research, 2025)
Background: In Pakistan, gall bladder related diseases like cholelithiasis impacts 10% to 15% of adults. Pain control measures remain vital in patients’ outcome improvement and the decreased use of analgesics after surgery. A locally adapted solution that will decrease pain and utilize fewer analgesics will be more helpful in limited access setting such as Pakistan where these additional resources in pain management may not be easily available. Aim: This research aims to explore the effects of saline instillation on pain relief by making comparison between postoperative pain levels and analgesic consumption patients who receive saline instillation and those who do not. Methodology: This comparative study aimed to assess the efficacy of intraperitoneal 1 liter normal saline instillation for pain management after laparoscopic cholecystectomy. Data were collected from February to September 2024 at a tertiary care hospital in Punjab, Pakistan, involving 70 patients (35 males, 35 females) undergoing elective cholecystectomy. Group A (Control) received standard surgery, while Group B received saline instillation. Pain intensity was measured using the VAS scale, and statistical analysis was performed using SPSS. Results and Conclusion: This study examined the effects of 1-liter normal saline instillation after laparoscopic cholecystectomy on postoperative pain and opioid use. Results showed that saline significantly reduced pain (mean score: 2.83 vs. 6.06) and analgesic consumption (50.29 mg vs. 91.14 mg) compared to the control group, offering better pain relief and lower medication usage.